Optimalisasi Nilai-Nilai Qur'ani Pra-Nikah Melalui Program BRUSIN (Bimbingan Remaja Usia Siap Nikah) pada Mahasiswa Universitas Yudharta Pasuruan - Fatchur Rozi, Mukhammad; Khamidiyah, Najwa Fibi; Hidayah, Nauval Rif’an; Nur Aini, Feni; Abdan, Ahmad Syarwani; Mahmud, Amir (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
A harmonious marriage is the goal of every couple who wants to build a sakinah, mawaddah and rahmah family. However, to achieve this goal, mental and spiritual readiness is needed which is based on Qur'anic values. Unfortunately, today's young generation often enters marriage without sufficient understanding of these values, making them vulnerable to domestic conflict. This article aims to describe the BRUSIN (Guidance for Young People Ready for Marriage) program as a form of community service aimed at Yudharta University students in order to optimize pre-marital Qur'anic values. This program includes lecture methods, intensified guidance, discussion forums, and ongoing monitoring using a PAR (Participatory Action Research) model approach. The results of the program can be seen from questionnaire data which shows an increase in understanding and internalization of Qur'anic values in participants, which is expected to be able to become the basis for building quality households.